Integrating SOGIESC Content into Mental Health Training Curricula: Enhancing Competency and Promoting Equity in India - Chinchu C (Journal of Psychosexual Health)
This article argues for the integration of Sexual Orientation, Gender Identity and Expression, and Sex Characteristics (SOGIESC) content into academic training of mental health professionals in India to address significant gaps in understanding and treatment of SOGIESC diverse individuals. Despite growing recognition of SOGIESC as critical determinants of mental health, current curricula often neglect these aspects, perpetuating biases that adversely affect diagnosis and care. This article highlights the structural inequalities faced by SOGIESC communities and the resultant impact on mental health outcomes, emphasising the need for a rights-based approach in mental health education. Through a comprehensive review of existing literature, this article identifies pervasive stereotypes and discrimination within healthcare settings that hinder effective treatment. It proposes a multi-stage integration pathway, beginning with audits of current curricula, followed by content development that incorporates SOGIESC awareness into training programmes for mental health professionals. This article advocates for participatory processes involving stakeholders from SOGIESC communities to ensure that training is relevant and effective. It is argued that enhancing competency in SOGIESC issues among mental health professionals is essential for fostering equitable care. By addressing both stigma related to mental health and discrimination based on sexual orientation or gender identity, this integration can contribute to a more inclusive healthcare landscape in India, aligning with the broader goal of achieving ‘health for all’.